APPLICATION OF COERCIVE MEASURES IN THE CIVIL PROCEEDINGS IN UZBEKISTAN - Davronov Doniyorbek Abdullo o`g`li (European Science Publishing, 2024)
This article deals with the concept, necessity, place and importance of coercive measures in civil proceedings, the grounds and procedure for the application of coercive measures, the application of coercive measures in civil proceedings. Problems related to the using of coercive procedural measures in the course of litigation, theoretical and practical issues of coercive procedural measures, analysis of civil procedure legislation of the Republic of Uzbekistan and its norms based on civil law of foreign countries, procedural experience of foreign countries coercive measures, proposals and recommendations on improving procedural coercive measures in civil proceedings.
Keywords: coercive measures, court fine, removal from the courtroom, coercion, compulsory attendance, warning, ruling, court protocol, court order.